Identification of causative organism in cardiac implantable electronic device infections. Issue 5 (November 2017) - Fukunaga, Masato; Goya, Masahiko; Nagashima, Michio; Hiroshima, Kenichi; Yamada, Takashi; An, Yoshimori; Hayashi, Kentaro; Makihara, Yu; Ohe, Masatsugu; Ichihashi, Kei; Ohtsuka, Morimasa; Miyazaki, Hiroaki; et al.
Abstract: Background: The causative organism in cardiovascular implantable electronic device (CIED) infection is usually diagnosed with the cultures from blood, removed leads, and/or infected pocket material. The cultured organism, however, is sometimes different among these samples. Methods: Two hundred sixty patients with CIED infection, who underwent lead extraction between April 2005 and December 2014, were analyzed. More than two blood culture sets, all the extracted leads, and swab culture of the pocket were sent to the laboratory for culture. Among the patients all of whose microbiological examinations were available, we analyzed the causative organism defined as the species detected in at least two different sites. Results: All the culture results were available in the 208 patients, showing 69 systemic infections (including 30 cases of infectious endocarditis) and 139 local infections. Blood culture, lead culture, and swab culture were positive in 57 (27%), 169 (81%), and 152 (73%), respectively. Staphylococcus aureus [37% including methicillin-resistant S. aureus (MRSA) (12%)] and coagulase-negative staphylococci (CoNS, 36%) were the most common causative organism, followed by non-staphylococci (23%), and poly-microbial infection (4%). The detection of S. aureus from pocket or removed leads rendered higher predictive value of a causative organism than that of CoNS. The detection of Gram-negative bacteria, fungi, and mycobacteria indicated that it was most likely a causative organism. Gram-positive bacteria excluding Staphylococcus, such as Corynebacterium spp., tended to coexist as a benign organism. Conclusions: The causative organism is mostly S. aureus and CoNS. Detection of S. aureus or Gram-negative bacteria means that it is more likely a causative organism.